2016
DOI: 10.3390/nu8010048
|View full text |Cite|
|
Sign up to set email alerts
|

Cancer Prevention and Health Benefices of Traditionally Consumed Borago officinalis Plants

Abstract: Nowadays, healthy eating is increasing the demand of functional foods by societies as sources of bioactive products with healthy qualities. For this reason, we tested the safety of the consumption of Borago officinalis L. and its main phenolic components as well as the possibility of its use as a nutraceutical plant to help in cancer prevention. The in vivo Drosophila Somatic Mutation and Recombination Test (SMART) and in vitro HL-60 human cell systems were performed, as well-recognized methods for testing gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 58 publications
2
26
0
1
Order By: Relevance
“…CCRF-CEM, CEM/ADR5000 leukemia cells treated with RA (3–100 μM) developed increased cytotoxicity, apoptosis, necrosis, cell cycle arrest and caspase-independent apoptosis which was mediated by increased PARP cleavage and blockage of p65 nuclear translocation [105]. In agreement with other studies, RA (0.07–2.2 mM) exerted DNA protective and anti-carcinogenic effects in HL-60 leukemia cells [106]. …”
Section: Anticancer Effects Of Rosmarinic Acid (Ra): In Vitro Studiessupporting
confidence: 78%
“…CCRF-CEM, CEM/ADR5000 leukemia cells treated with RA (3–100 μM) developed increased cytotoxicity, apoptosis, necrosis, cell cycle arrest and caspase-independent apoptosis which was mediated by increased PARP cleavage and blockage of p65 nuclear translocation [105]. In agreement with other studies, RA (0.07–2.2 mM) exerted DNA protective and anti-carcinogenic effects in HL-60 leukemia cells [106]. …”
Section: Anticancer Effects Of Rosmarinic Acid (Ra): In Vitro Studiessupporting
confidence: 78%
“…We have also demonstrated that the increased ROS production and reduced GSH concentration in kidney cells in groups was fed HF and HFF, has resulted in compromised mitochondrial bioenergetics , resulted in inhibition of the activities of the respiratory complexes followed by a reduction in ATP synthesis finally lead to increased mitochondrial dysfunction [28].In the current study there were significant decreases in kidney PON1and GSH level and a significant increase in kidney MDA and NO in HFF and HF compared to LF. These results were in agreement with Lozano et al [29] who indicated that generation of free radicals promotes lipid peroxidation in HF and HFF groups. In agreement with…”
Section: Discussionsupporting
confidence: 93%
“…A similar effect was observed in Cordia verbenacea trichomes and in powdered Sericostoma pauciflorum Stocks raw material (Ventrella and Marinho, 2008;Kevalia et al, 2015). The content of phenolic compounds is associated with antioxidant, antimicrobial, anticancer, and cytotoxic properties of borage (Zemmouri, 2014;Lozano-Baena et al, 2016). The compounds also have economic importance, as they determine the quality of food: color, odor, and flavor.…”
Section: Histochemical Assaysmentioning
confidence: 99%